ISOLASI FLAVONOID DARI DAUN KETAPANG (TERMINALIA CATAPPA L.) - Hatmoko, Puji
Ketapang (Terminalia catappa L.) is one of Indonesian plant that mostly distributed in Java island. Almost all parts of the plant were used as traditional medicine by Indonesian people. This makes the study of chemical compounds of Ketapang prospectively explore. The plant part of Ketapang that commonly used as traditional medicine is leaves which has a pharmacological effect as an diaforetikum . Previous research showed that Ketapang leaves contain phenolic and flavonoid compounds (quercetine). This study aimed to isolate and characterize flavonoid contained in Ketapang leaves. Methods:Crude drug of Ketapang leaves was extracted using methanol by reflux method and monitored by thin layer chromatography (TLC). Hot water was added into the extract and filtered to remove chlorophyll, the filtrate was then fractionated by liquid-liquid extraction method using n- hexane and ethyl acetate. The ethyl acetate fraction was subfractionated by radial chromatography with gradient elution using n-hexane, ethyl acetate and methanol. The - subfraction which containing flavonoid was purified by preparative TLC. the obtained compound was tested for its purity by TLC using three different mobile phase and two dimensional TLC The isolate was characterized by UV-Vis Spectrophotometry, two dimensional paper chromatography, and shifting reagents. Crude drug of Ketapang leaves contained alkaloids, flavonoids, steroids and triterpenoids.The flavonoid compound was isolated from the ethyl acetate fraction It showed Rf values of 0.23 (mobile phase: n- butanol-acetic acid-water, 4:1:5) and 0.21 (mobile phase: acetic acid 15%) by paper chromatography method. The isolate gave maximum UV absorbance in wavelength of 271 nm (Band II) and 328 nm (Band I). The band I shifted 70 nm with NaOH. The isolated compound was predicted as a flavone-O-monoglycoside, which contained OH group in C4’.